THE POTENTIAL OF GROWING TAXA OF AKEBIA QUINATA (HOUTT.) DECNE. UNDER THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - Elisaveta Onica (Agricultura, 2020)
The bioecological features and the peculiarities of propagation and cultivation of the introduced species – Akebia quinata (Houtt.) Decne. under the climatic conditions of the Republic of Moldova are described below. Most organs of this plant contain biologically active substances with beneficial therapeutic effects and can serve as a raw material for the food and pharmaceutical industry. Layering is the optimal means of propagation for obtaining high quality planting material with desired characteristics. As an ornamental species, it can be grown in groups, in gardens, to decorate pergolas, railings, walls or even dry trees, since it maintains its attractive appearance throughout the growing season.